Analisis Kinerja Keuangan Pada PT. Unilever Indonesia Tbk - Jefri Yanto Cahya Putra (Publikasi Indonesia, 2023)
Financial ratios become an illustration in consideration materials to explain between the values in the financial statements. All aspects of the business sector are very important in paying attention to financial management both in banking, industry, manufacturing, and retail. This is because the financial sector applies financial principles in an institution with the aim of creating optimal value to make decisions and manage resources owned by the company appropriately. The method in this study uses data analysis based on financial statements by measuring, knowing, illustrating, and comparing charts in financial statements, especially the balance sheet and profit and loss. Ratio analysis uses a method of financial statement analysis that looks at a certain period of years, then compares with financial statements with different years through sections of the financial statements. From the results of the research conducted, the Company's Performance of PT Unilever Indonesia Tbk based on the Profitability Ratio in 2021 and 2022 decreased and the Financial Performance of PT Unilever Indonesia Tbk based on the Liquidity Ratio also decreased in 2021 and 2022.